2010
DOI: 10.1007/s10811-010-9532-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on the biochemical composition of the alga Botryococcus braunii Kütz IPPAS H-252

Abstract: The effect of 0.3 and 0.7 M NaCl on biomass yield, total nitrogen content, intracellular lipid content, and fatty acid profile of the lipids of the alga Botryococcus braunii IPPAS H-252 in different phases of the culture cycle was studied. The presence of sodium chloride in the medium inhibited the growth of algal cells for the first 3 days of the experiment, causing a decrease in total nitrogen, enhanced synthesis of triacylglycerols, and considerable changes in the lipid fatty acid profile: decreases in poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 21 publications
(25 reference statements)
3
56
0
6
Order By: Relevance
“…The quantity and quality of fatty acids content as well as the entire biochemical composition varies in response to environmental conditions 8,20,24,25,38,39 . Particularly, under unfavorable environmental or stress conditions for growth, such as salinity, temperature, pH, and nutrient levels, many algae alter their lipid biosynthetic pathways towards the formation and accumulation of neutral lipids to control intracellular stress 13,40 .…”
Section: Discussionmentioning
confidence: 99%
“…The quantity and quality of fatty acids content as well as the entire biochemical composition varies in response to environmental conditions 8,20,24,25,38,39 . Particularly, under unfavorable environmental or stress conditions for growth, such as salinity, temperature, pH, and nutrient levels, many algae alter their lipid biosynthetic pathways towards the formation and accumulation of neutral lipids to control intracellular stress 13,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Exposing algae to lower or higher salinity levels than their natural (or adapted) levels can change growth rate and alter composition. For example, higher salinity increases the algae lipid content [141][142][143][144]. Dunaliella, a marine alga, exhibited an increase in saturated and monounsaturated fatty acids with an increase in NaCl concentration from 0.4 to 4 M [145].…”
Section: Salinitymentioning
confidence: 99%
“…To resist the osmotic pressure, an increase in membrane lipid content naturally reduces the TAG percentage from membrane lipid transformation (Chen et al, 2008), and the increased total lipid mainly comprise polar lipids, not TAG (Azachi et al, 2002;Chen et al, 2008). However, this condition is inconsistent with the transformation relationships among NL, PL and GL (Chen et al, 2008;Zhila et al, 2011). The effect of NaCl induction is closely related to the growth stage of microalgae.…”
Section: Introductionmentioning
confidence: 99%
“…However, these assumptions are physiological speculations and are inconsistent with the lipid class transformation observed in other algae. Zhila et al (2011) reported that Botryococcus braunii Kütz IPPAS H-252 could increase lipid and TAG along with increasing salt stress. Chen et al (2008) found that TAG of Nitzschia laevis decreased but the PL increased in heterotrophic cultures at high NaCl concentrations.…”
mentioning
confidence: 99%